2001
DOI: 10.4315/0362-028x-64.8.1188
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Testing of Ready-to-Eat Meat and Poultry Products Collected at Federally Inspected Establishments in the United States, 1990 to 1999

Abstract: The Food Safety and Inspection Service (FSIS) conducted microbiological testing programs for ready-to-eat (RTE) meat and poultry products produced at approximately 1,800 federally inspected establishments. All samples were collected at production facilities and not at retail. We report results here for the years 1990 through 1999. Prevalence data for Salmonella, Listeria monocytogenes, Escherichia coli O157:H7, or staphylococcal enterotoxins in nine different categories of RTE meat and poultry products are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
1
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(75 citation statements)
references
References 2 publications
5
61
1
6
Order By: Relevance
“…Foodborne pathogens such as Salmonella and Listeria monocytogenes have been detected in finished dry and semidry fermented sausages, including Italian-style salami, rendering the consumption of these ready-to-eat (RTE) products a potential food safety risk (20,23). In 1999, Mead et al (22) estimated that 50% of deaths due to known foodborne pathogens could be attributed to Salmonella or L. monocytogenes infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foodborne pathogens such as Salmonella and Listeria monocytogenes have been detected in finished dry and semidry fermented sausages, including Italian-style salami, rendering the consumption of these ready-to-eat (RTE) products a potential food safety risk (20,23). In 1999, Mead et al (22) estimated that 50% of deaths due to known foodborne pathogens could be attributed to Salmonella or L. monocytogenes infections.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the Italian-style salami manufacturing process evaluated does not adequately reduce high pathogen loads. Processors may thus need to consider supplemental measures, such as raw material specifications and a final heating step, to enhance the lethality of the overall manufacturing process.Foodborne pathogens such as Salmonella and Listeria monocytogenes have been detected in finished dry and semidry fermented sausages, including Italian-style salami, rendering the consumption of these ready-to-eat (RTE) products a potential food safety risk (20,23). In 1999, Mead et al (22) estimated that 50% of deaths due to known foodborne pathogens could be attributed to Salmonella or L. monocytogenes infections.…”
mentioning
confidence: 99%
“…The eight categories of food surveyed were luncheon meats, deli salads, fresh soft "Hispanic-style" cheese, bagged salads, blue-veined cheese, soft mold-ripened cheese, smoked seafood, and seafood salads. Surveillance and monitoring activities of the FDA and U.S. Department of Agriculture in the mid-1990s indicated that up to 5% of some RTE foods, such as prepared deli salads and luncheon meats, may contain L. monocytogenes (17,19). The other six food categories were chosen by Gombas et al (13) to provide additional data for risk assessment.…”
mentioning
confidence: 99%
“…In USA it was proven that the cumulative 3-y L.monocytogenes prevalence for dry and semidry fermented sausages was 3.25%. This kind of sausages is very popular also in Bulgaria and 4 of 10 of our L.monocytogenes isolates were isolated from this type of raw cured dried product (13). Opinion was noted that processing facilities were frequently contaminated with nonpersistent or persistent L. monocytogenes, which played an important role in contamination of the products.…”
Section: Discussionmentioning
confidence: 99%